(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Background: Neurological disorders constitute approximately 30% of all diseases globally, with a significant majority prevalent in developing nations. Aim: This study focuses on assessing the health-related quality of life (HRQoL) in pediatric patients subjected to neurosurgery. Methods: Clinical data were procured from different hospitals in Iraq during the period between July 14th, 2022, and August 18th, 2023, involving both pediatric and adult patients undergoing neurosurgery. The study encompassed 67 patients with an age range of 2 to 13 years. The data included test results and identified etiology in children.